Reconstitution of defective protein trafficking rescues Long-QT syndrome in zebrafish - Meder, Benjamin; Scholz, Eberhard P.; Hassel, David; Wolff, Christoph; Just, Steffen; Berger, Ina Maria; Patzel, Eva; Karle, Christoph; Katus, Hugo; Rottbauer, Wolfgang (Biochemical and biophysical research communications, 2011)
Inherited cardiac arrhythmias are caused by genetic defects in ion channels and associated proteins. Mutations in these channels often do not affect their biophysical properties, but rather interfere with their trafficking to the cell membrane. Accordingly, strategies that could reroute the mutated channels to the membrane should be sufficient to restore the electrical properties of the affected cells, thereby suppressing the underlying arrhythmia. We identified here both, embryonic and adult zebrafish breakdance (bre) as a valuable model for human Long-QT syndrome. Electrocardiograms of adult homozygous bre mutants exhibit significant QT prolongation caused by delayed repolarization of the ventricle. We further show that the bre mutation (zERGI59S) disrupts ERG protein trafficking, thereby reducing the amount of active potassium channels on the cell membrane. Interestingly, improvement of channel trafficking by cisapride or dimethylsulfoxid is sufficient to reconstitute ERG channels on the cell membrane in a manner that suffices to suppress the Long-QT induced arrhythmia in breakdance mutant zebrafish. In summary, we show for the first time that therapeutic intervention can cure protein trafficking defects and the associated cardiac arrhythmia in vivo.
Gesehen am 15.09.2022